Patient-specific instrumentation and custom total knee implants in total knee arthroplasty. Issue 3 (May 2015) - Isaacson, Mark; Bunn, Kevin; Incavo, Stephen
<x xml:space="preserve">Abstract</x> Total knee arthroplasty (TKA) is a successful operation improving quality of life for patients. As demand for TKA increases, surgeons and healthcare systems search for a cost-effective method that provides improved patient outcomes. Computer navigation and robotic systems were introduced to refine mechanical alignment, but broad acceptance has been limited due to the cost of implementation and increased operating room time. Patient-specific instrumentation (PSI) was similarly designed to restore kinematic alignment. Several orthopaedic implant manufacturers offer such instruments. Preoperative imaging is required and submitted to the manufacturer. A computer simulation of the knee anatomy is generated, and bone resections are planned using their proprietary software. Femoral or tibial cutting blocks are then fabricated. Approximate time from surgeon approval of the computer-simulated plan to delivery of custom instruments is 3-6 wk. Proposed benefits of these technologies include cost savings from improved efficiency in the operating room, improved implant alignment, and patient outcome. Disadvantages include increased cost from preoperative 3D imaging and fabrication of instruments, increased workload for surgeon and staff, and the learning curve. Current literature on the use of PSI technologies in TKA reveals no agreement on the value of PSI technologies. Additional study of these technologies is recommended before broad acceptance and universal use is achieved.